Development of synthetic membrane transporters for anions - Davis, Anthony P. (2006)
The development of low molecular weight anion transporters is an emerging topic in supramolecular chemistry. The major focus of this tutorial review is on synthetic chloride transport systems that operate in vesicle and cell membranes. The transporters alter transmembrane concentration gradients, and thus they have applications as reagents for cell biology research and as potential chemotherapeutic agents. The molecular designs include monomolecular channels, self-assembled channels and mobile carriers. Also discussed are the experimental assays that measure transport rates across model bilayer membranes.